Efficiency of Air Transport Industry in European Union Nations with Regard to Environmental Factors - Tunahan Avcı; Tuğba Akbıyık (Verimlilik Dergisi)
Purpose: Evaluating the effectiveness of nations by analyzing the relationship between the outcomes of the aviation sector and the environmental resources associated with these outcomes is essential for policymakers to develop environmental regulations and for managers to take suitable actions. This study aims to evaluate the environmental effectiveness of the airline industry in European Union (EU) member states.Methodology: We assessed the efficiency of data from 26 EU countries using Data Envelopment Analysis.Findings: The study's findings determined that Austria, Luxembourg, Hungary, and Ireland had the lowest efficiency levels. Air pollution and greenhouse gas emissions primarily influence the efficiency of these countries. We identify Germany as the least efficient country, specifically when compared to France and Italy. These findings indicate that, despite the EU's implementation of environmental impact legislation, developed member states have not successfully enforced it.Originality: Previous research has not examined the effectiveness of countries in terms of both passenger and flight volumes, as well as environmental considerations such as air pollution, greenhouse gas emissions, kerosene and jet fuel use, energy products, and overall environmental taxation